Testing the agreement of medical instruments: overestimation of bias in the Bland Altman analysis - Zaki, R.; Bulgiba, A.; Ismail, N.A. (2013)
Background: Despite the continuous efforts to improve the quality of life of Orang Asli (Aborigines) communities, these communities are still plagued with a wide range of health problems including parasitic infections. The first part of this study aimed at determining the prevalence of soil-transmitted helminth (STH) infections and identifying their associated factors among rural Orang Asli children. Methods: A cross-sectional study was carried out among 484 Orang Asli children aged 15 years (235 females and 249 males) belonging to 215 households from 13 villages in Lipis district, Pahang, Malaysia. Faecal samples were collected and examined by using formalin-ether sedimentation, Kato Katz and Harada Mori techniques. Demographic, socioeconomic, environmental and behavioural information were collected by using a pre-tested questionnaire. Results: Overall, 78.1 of the children were found to be infected with one or more STH species. The prevalence of trichuriasis, ascariasis and hookworm infections were 71.7, 37.4 and 17.6, respectively. Almost all, three quarters and one fifth of trichuriasis, ascariasis and hookworm infections, respectively, were of moderate-to-heavy intensities. Multiple logistic regression analysis showed that age of years (school-age), using unsafe water supply as a source for drinking water, absence of a toilet in the house, large family size ( 7 members), not washing hands before eating, and not washing hands after defecation were the key factors significantly associated with STH among these children. Conclusion: This study reveals an alarmingly high prevalence of STH among Orang Asli children and clearly brings out an urgent need to implement school-based de-worming programmes and other control measures like providing a proper sanitation, as well as a treated drinking water supply and proper health education regarding good personal hygiene practices. Such an integrated control program will help significantly in reducing the prevalence and intensity of STH in Orang Asli communities.